2014
DOI: 10.1177/0148558x14537824
|View full text |Cite
|
Sign up to set email alerts
|

Goodwill Impairment Losses and CEO Compensation

Abstract: Corporate acquisitions are arguably one of the most important and biggest decisions CEOs have to make; yet many acquisitions do not create value for shareholders. We examine whether CEO compensation is reduced when the fair values of the acquired business units are written down (i.e., goodwill impairment losses are recognized). We find that there is a significant reduction in cash-and option-based CEO compensation as firms recognize goodwill impairment losses. In particular, we find that the decrease in CEO op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 54 publications
2
33
1
1
Order By: Relevance
“…The analysis of scientific literature allowed discovering a great deal of research proving that company managers have the greatest influence on making decisions whether or not to disclose goodwill impairment and many reasons impact the decisions that are reached by company managers (Lemans, 2010;Ramana & Watts, 2011;Saastamoinen & Pajunen, 2012;Iatridi & Senftlechner, 2014;Darrough et al, 2014;Giner & Pardo, 2014;Jordan & Clark, 2015).…”
Section: Factors Influencing Goodwill Impairmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of scientific literature allowed discovering a great deal of research proving that company managers have the greatest influence on making decisions whether or not to disclose goodwill impairment and many reasons impact the decisions that are reached by company managers (Lemans, 2010;Ramana & Watts, 2011;Saastamoinen & Pajunen, 2012;Iatridi & Senftlechner, 2014;Darrough et al, 2014;Giner & Pardo, 2014;Jordan & Clark, 2015).…”
Section: Factors Influencing Goodwill Impairmentmentioning
confidence: 99%
“…The binary logistic regression model, which was also applied by scientists Verriest & Gaeremynck (2009), Bepari et al (2011), Darrough et al (2014) in order to research goodwill impairment decisions, is written down in the following manner:…”
Section: Development and Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the unverifiability of fair-value estimation, the new standard has increased the discretionary power of managers. Based on the unverifiable discretion of the goodwill impairment test, many scholars have conducted in-depth studies on the motivations of managers to recognize goodwill impairment (Beatty & Weber, 2006;Lapointe-Antunes et al, 2008;AbuGhazaleh et al, 2011;Hamberg et al, 2011;Onesti & Romano, 2012;Ramana & Watts, 2012;Giner & Pardo, 2015;Iatridi & Senftlechner, 2014;Filip et al, 2015;Li & Sloan, 2017;Glaum et al, 2018), information transmitted by goodwill impairment (Holthausen & Watts ;Bens et al, 2011;Bostwick et al, 2015;Knauer, 2016;Qu et al, 2017), and the consequences of recognizing goodwill impairment (Darrough et al, 2014;Rehman & Shahzad, 2014;Qu et al, 2017). Beatty & Weber (2006) specifically examined the motivations of managers to recognize goodwill impairment.…”
Section: Literature On Goodwill Impairmentmentioning
confidence: 99%
“…Less research has examined the consequences of goodwill impairment for companies. Darrough et al (2014) found that when a company recognizes the impairment of goodwill, the CEO's cash compensation and option salary will decrease. In addition, Carcello et al (2019) showed that the probability of auditor dismissal is associated with goodwill impairment, Ayres et al(2019) indicated that the non-audit fees a client pays are inversely related to the likelihood of impairment in settings where goodwill is likely to be impaired..…”
Section: Literature On Goodwill Impairmentmentioning
confidence: 99%